Restructuring the Gene Ontology to emphasise regulative pathways and to improve gene similarity queries. (22nd July 2011) - Visconti, Alessia; Esposito, Roberto; Cordero, Francesca
The Gene Ontology (GO) has been developed to provide a structured vocabulary for genes description. Conversely, gene functional similarity measures would benefit from a structure tailored to emphasise genes involved in the same biological context. Therefore, such measures often find it difficult to fully exploit the information in the GO. This paper reorganises the GO to emphasise regulative information thus providing a better structure for functional analysis. A gene functional similarity measure exploiting the new structure is proposed. Empirical evidence shows that the new structure correctly captures regulative processes and that it can be used to support the proposed measure.